2013
DOI: 10.1186/2191-219x-3-71
|View full text |Cite
|
Sign up to set email alerts
|

Explorative analyses on the value of interim PET for prediction of response in pediatric and adolescent non-Hodgkin lymphoma patients

Abstract: BackgroundThis study is to evaluate the predictive value of FDG-PET (PET) in pediatric and adolescent patients suffering from non-Hodgkin lymphoma (pNHL) in comparison to information provided by conventional imaging methods (CIM).MethodsImaging was performed at baseline and at interim (after 2 cycles of chemotherapy). The response assessment in PET was carried out visually and semi-quantitatively, the latter one by use of percentage decrease in SUVmax from baseline to interim (ΔSUVmax). The PET-based results w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
2
7
0
Order By: Relevance
“…4 In our study, the 18 FDG-PET sensitivity was 88.2% and the NPV was 86.6%. Similar results have been reported with an NPV of 80% to 100%, 10,11 making it a very good negative test and a reliable indicator of CR, 13,14 and suggesting the possibility to avoid biopsy from a residual mass if it is negative. 8,9,[15][16][17] FN results varied among different studies and ranged from 0% to 5%.…”
Section: Discussionsupporting
confidence: 85%
“…4 In our study, the 18 FDG-PET sensitivity was 88.2% and the NPV was 86.6%. Similar results have been reported with an NPV of 80% to 100%, 10,11 making it a very good negative test and a reliable indicator of CR, 13,14 and suggesting the possibility to avoid biopsy from a residual mass if it is negative. 8,9,[15][16][17] FN results varied among different studies and ranged from 0% to 5%.…”
Section: Discussionsupporting
confidence: 85%
“…However, interim 18 F-FDG PET/CT scans after 2-3 cycles of standard chemotherapy showed a relatively wide range of sensitivity (77.8%-100%) and specificity (54.5%-97.7%) ( Table 1) (26,38,45,46). This may be due to lack of consensus on the best timing of interim PET and the definition of objective response criteria for interpretation (47)(48)(49). Nevertheless, interim 18 F-FDG PET/CT has shown high negative predictive value, and therefore an early negative scan is a reliable indicator for therapy response (negative predictive value, 85.7%-100%; positive predictive value, 41.2%-85.7%) (26,38,45).…”
Section: Therapy Response Assessmentmentioning
confidence: 86%
“…The few studies previously performed on pediatric lymphomas patients ( 16 22 ) demonstrated a good NPV of 18 FDG-PET performed during treatment, with values ranging from 85 to 100% suggesting biopsy can be avoided if 18 FDG-PET was negative. The recent pediatric study by Furth et al ( 17 ) was conducted on 16 pediatric NHL patients and showed an overall NPV of 85.7%, rising to 100% when considering only BL ( n = 7). Similarly, studies dedicated to pediatric BL by Karantanis et al ( 23 ) and Riad et al ( 25 ) reported a 100% NPV of 18 FDG-PET after chemotherapy despite residual masses detected on CI.…”
Section: Discussionmentioning
confidence: 99%
“…Riad et al ( 25 ) described false-positive 18 FDG uptake in four of 28 pediatric patients with abdominal BL. In these studies, abnormal 18 FDG uptake was variously defined: uptake greater than background activity in surrounding tissue ( 19 , 23 , 24 ), or the mediastinal blood pool activity ( 17 ) or IHP criteria ( 18 ) for reference. In our study, 18 FDG-PET images were interpreted with the current consensual set of criteria recently recommended by the “Lugano recommendations” ( 10 , 11 ).…”
Section: Discussionmentioning
confidence: 99%